Effect of a novel dwarfing mutant site on chromosome 4B on agronomic traits in common wheat - Hao, Jiamin; Zhao, Zhangchen; Fu, Xiaoge; Zhao, Yujiao; Ateeq, Muhammad; Mou, Liming; Han, Yong; Liu, Yangbin; Yin, Yongan; Zotova, Lyudmila; Serikbay, Dauren; Fan, Chunyan; et al. (Frontiers in Plant Science, 2024)
The introduction of dwarfing genes triggered a wave of "green revolution". A number of wheats dwarfing genes have been reported in previous studies, and only a small fraction of these have been applied to production practices. Therefore, the development of novel dwarfing genes for wheat is of great value. In this study, a novel dwarfing site, Rht-yz, identified in the Yanzhan mutation, is located on chromosome 4B (30-33MB) and its mechanism of action is different from that of Rht-B1b (C-T mutation), but whether it affects the Rht-B1a (TraesCS4B02G043100) or other genes is unclear. Exogenously applied GA3 experiments showed that Rht-yz is one of the gibberellin-insensitive dwarf genes. The effects of the dwarf gene Rht-yz on agronomic traits in wheat were evaluated in the field using Yanzhan, Yanzhan mutations, F2:3 and F3:4 lines. The results showed that Rht-yz improved lodging resistance by reducing plant height, increasing diameter, wall thickness and mechanical strength of the basal stem. In terms of yield traits, Rht-yz had negative effects on tiller number plant-1, biomass plant-1 and yield plant-1, but had no significant effect on harvest index, 1000-kernel weight and spike traits. In addition, Rht-yz significantly increased crude protein, wet gluten and starch content. Therefore, the rational use of the new dwarfing site Rht-yz has potential and value in dwarf wheat breeding.